What is the impact of weather shocks on prices? - Hill, Ruth Vargas,Fuje, Habtamu (World Bank Group, Poverty and Equity Global Practice, 2020)
The impact of drought on household welfare is the cumulative effect of crop losses and price changes in a local economy that are triggered by these initial losses. This paper combines data on monthly grain prices and wages in 82 retail markets over 17 years with data on district-level weather shocks to quantify the impact of drought on local prices and how this impact varies by month after harvest. The results show that price increases occur immediately after the completion of harvest and then dissipate so that inflationary effects are quite low during the lean season, contrary to commonly held views. The impact of shocks on prices is quite low now in Ethiopia - 4 percent at its peak post-2005 compared with 12 percent before 2005. In areas of the country where infrastructure investments have been high, there is now almost no inflationary impact of drought on prices. It is not clear whether it is infrastructure investments or something else that has driven that, but it shows that it is possible for rainfall shocks to have no inflationary impacts in low income economies. Inflationary impacts were also reduced more in districts where the Productive Safety Net Program was introduced. Comparing inflationary effects in districts with food versus cash transfers suggests that cash transfers do not have inflationary effects on grain prices during times of drought
10.1596/1813-9450-9389
Keywords: Graue Literatur; Weather shocks; grain markets; seasonality; transfers; roads